Using a mouse model to understand the effect of hybridization on skeletal and pelage trait variation in mammalian hybrids - Humphreys, Robyn (Department of Archaeology, 2019)
Hybridization is thought to have played an important role in human evolution, with hybridizing groups having significant differences in soft tissue trait variation. Ectodermal trait variation is of interest because primate hybrids show increased atypical non-metric dental and cranial trait variation thought to be the result of interactions between parental genomes which have diverged for ectodermal trait development (including hair and tooth development). There were also differences between hybridizing hominin groups for limb measurements which have changed significantly throughout human evolution. Here a mouse model is used to look at the effect of hybridization on coat morphology and long bone length. Using standardized photographs, the differences in mean RGB values for the dorsal and ventral coat were used to determine whether the hybrids were different from their parents for pelage colour of different regions of the body, dorsal ventral colour contrast, and levels of variation in coat colour. The sample is composed of parents from one specific and three sub-specific crosses, as well as F1, F2 and first generation backcrossed (B1) hybrids. Long bone measurements of the forelimbs and hind-limbs were collected from micro-CT scans of the sub-specific F1 hybrids and their parents. Previous data have shown that hybridization can have variable morphological outcomes: hybrids can look like one of the parents, they can be intermediate, or they can have extreme traits outside of the range of variation of the parents. Our results indicate that morphological outcomes for coat colour in F1 hybrids depends on factors such as genetic distance. However, the genetic background of one of the strains used for this experiment might contribute the transgressive phenotype of some of the F1 hybrids. Hybrid morphology also changes in subsequent generations (F2 and B1) as new recombinants formed, with transgressive coat colour phenotypes sometimes appearing even if they are not present in the F1 hybrid groups. Phenotypes produced in F1 hybrids are also seen in subsequent generations of hybrids. All sub-specific F1 hybrids were transgressive for long bone length. Compared to parental groups hybrids have a different relationship between the long bones of the forelimb (ratio of humerus to ulna). This is in line with previous data from primate hybrids, that shows that changes in the relationships between different regions of the body occurs in hybrids producing novel phenotypes. The inter-membral indexes are not significantly different from one of the parents for two of the crosses. This data shows that hybridization can produce novel pelage phenotypes over multiple generations. There were many transitions in hair/skin morphology during human evolution and these tissue groups were and are under a great deal of selective pressure due to their direct interaction with the environment. Thus, understanding how these traits are impacted by hybridization will be important for disentangling how hybridization affected our evolutionary trajectory and ability to occupy new regions of the world. Post cranial data, indicates that F1 hominin hybrids might have longer limbs in relation to parental populations, more work needs to be done on the post cranial remains of posited hominin hybrids as well as pedigreed mammalian hybrids to determine if this is a pattern which can be used to identify hybrids in the fossil record.